The Influence of Product Quality, Brand Image, and Celebrity Endorser on Purchase Decision (A Study on Somethinc Skincare) - Fabiola, Christalia; Indrajaya, Sonny (Dinasti Publisher, 2025)
The study aims to analyze the influence of product quality, brand image, and celebrity endorser on purchase decision of skincare Somethinc, and the object of the study is the user of product in the Bekasi area. The design of the study uses a quantitative approach with sampling using purposive sampling on 160 respondents. The data collection methode uses the survey method, with the research instrument is a questionnaire. Data processing is done using partial least squares (PLS) through the SMARTPLS 3.0 statistical software, and the analytical method used a structural equation modeling (SEM). The findings of this study indicate that product quality has a positive and significant impact on purchase decisions. Furthermore, brand perception also contributes positively and significantly to consumer choices. The presence of a celebrity endorser similarly exerts a positive and significant influence on purchasing decisions